Hubungan Tingkat Kecemasan dan Intensitas Nyeri dengan Kualitas Tidur Pasien Pasca Laparatomi di Ruang Rawat Inap RSUD Nurdin Hamzah - M, Rino; Fithriyani, Fithriyani; Putri, Miko Eka; Kadri, Hasyim (Jurnal Akademika Baiturrahim Jambi, 2025)
Laparotomy is a major surgical procedure, which involves incisions in the layers of the abdominal wall to obtain parts of the abdominal organs that are experiencing problems such as hemorrhage, perforation, cancer and obstruction. This research is a quantitative study conducted to determine the relationship between anxiety levels and pain intensity with the sleep quality of post-laparotomy patients in the inpatient room at Nurdin Hamzah Regional Hospital. The research design in this study is Cross Sectional. This research was conducted on December 5 2022 to January 5 2023 with a population of 144 with a sample of 30 respondents. The data collection method was carried out by filling out a questionnaire and univariate and bivariate analysis methods using the Chi-Square test. The results of the description of anxiety were 16 people (53.3%), the description of mild pain intensity was 15 people (50%), the Chi-Square test results obtained p value = 0.008 < (0.05), meaning there was There is a relationship between the level of anxiety and the sleep quality of patients after Laparotomy surgery in the Inpatient Room at Nurdin Hamzah Regional Hospital and the results of the Chi-Square test obtained a p value = 0.006 < (0.05), meaning that there is a relationship between pain intensity and sleep quality for patients after Laparotomy surgery. In the Inpatient Room at Nurdin Hamzah Regional Hospital, it is hoped that this research can provide a basis for knowledge regarding anxiety levels and sleep quality in patients after laparotomy surgery.